In-Vivo Effectiveness of 5% Azadirachta indica Oil Cream as Anti-Scabies - Patihul Husni; Mayang K. Dewi; Norisca A. Putriana; Rini Hendriani (Universitas Padjadjaran, Indonesia)
Scabies is an infectious skin disease caused by mite Sarcoptes scabiei. Neem tree (Azadirachta indica) has the potential to be used as an anti-parasite due to the presence of azadirachtin compound that is commonly found in the seeds. The aim of this study was to evaluate in-vivo effectiveness of neem oil as an anti-scabies. This study used an experimental method. The effectiveness of the cream as an anti-scabies was tested on New Zealand white rabbits which were infected with scabies. Permethrin cream was used as a positive control and cream base was used as a negative control. Cream was applied once daily and left for 8 hours. The data were analyzed using Kruskal Wallis and Mann Whitney. Dermal acute irritation test was performed by applying 0.5 g cream on the rabbit dorsal. We found that 5% neem oil cream was effective as an anti-scabies with 20-21 days recovery time. The recovery time is longer than permethrin cream (7-8 days), but shorter compared to negative control with recovery time over 30 days. Primary irritation index for 5% neem oil creams was 0, indicating negligible irritation category. In conclusion, A. indica cream was effective for the treatment of scabies although its recovery time is shorter than permethrin cream. Keywords: effectiveness test, irritation test, neem oil cream, scabies